2014
DOI: 10.15672/hjms.2014187469
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Class Of Estimators For Population Median Using Auxiliary Information

Abstract: This article suggests a generalized class of estimators for population median of the study variable in simple random sampling using information on an auxiliary variable. Asymptotic expressions of bias and mean square error of the proposed class of estimators have been obtained. Asymptotic optimum estimator has been investigated along with its approximate mean square error. It has been shown that proposed generalized class of estimators are more efficient than estimators considered by [26]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…7. Proposed median estimator in stratied random sampling Motivated by Singh and Solanki [14], Jhajj et al [7], Sharma and Singh [12], Aladag and Cingi [3] and Solanki and Singh [15], we propose the following general class of dierence type estimators for My in stratied random sampling:…”
Section: Numerical Study In Simple Random Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…7. Proposed median estimator in stratied random sampling Motivated by Singh and Solanki [14], Jhajj et al [7], Sharma and Singh [12], Aladag and Cingi [3] and Solanki and Singh [15], we propose the following general class of dierence type estimators for My in stratied random sampling:…”
Section: Numerical Study In Simple Random Samplingmentioning
confidence: 99%
“…Gupta et al [5] have suggested a class of estimators for population median using two auxiliary variables. Other important contributions in this area include Al and Cingi [2], Singh and Solanki [14], Jhajj et al [7], Sharma and Singh [12], Solanki and Singh [15] and Aladag and Cingi [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [7] proposed number of difference types estimators for population median using the supplementary variables. Other important contributions in this area include, Aladag and Cingi [8], Singh and Solanki [9], Jhajj et al [10], Sharma and Singh [11], Aladag and Cingi [12], Shabbir and Gupta [13,14], Solanki and Singh [15], Enang et al [16], Jhajj et al [17], Koyuncu [18], Irfan et al [19], Yadav et al [20], Bandyopadhyay et el. [21], Javed et al [22] and Baig et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…While the problem of estimating a population mean in the presence of an auxiliary variable has been widely discussed in the finite population sampling literature, relatively less effort has been devoted to the development of efficient methods for estimating a finite population median. Chambers and Dunstan (1986), Kuk and Mak (1989), Mak and Kuk (1993), Rao et al (1990), Meeden and Vardeman (1991), Meeden (1995), Garcia and Cebrian (2001), Singh et al (2001, Rueda and Arcos (2002), Allen et al (2002), Singh and Puertas (2003), , Singh, Sidhu and Singh (2006), Singh, Singh and Puertas (2006), Singh, Tailor, Singh and Kim (2007), Singh and Solanki (2013) and Sharma and Singh (2014) addressed the importance of estimating the population median in the presence of an auxiliary variable.…”
Section: Introductionmentioning
confidence: 99%